Subjective Assessments of the Disease Seriousness in the Population Aged 60+ - Doležalová, Jitka; Tóthová, Valérie; Neugebauer, Jan (Magyar Gerontológia, 2021)
The population aged 60+ constitute a considerable part of patients needing nursing care. A subjective assessment represents an important aspect that needs to be respected in nursing care and included in the care provided. The goal of the paper is to draw attention to the importance of a subjective assessment in the population aged 60+. Method: The study was performed in the South Bohemian Region. The study was quantitative and this part was carried out using a non-standardized questionnaire. The questions were particularly focused on the assessment of the social situation, health and everyday activities. The study was focused on the population aged 60+; it included the total number of 498 respondents. Results: Motor diseases, followed by cardiovascular and respiratory diseases, were perceived as the most serious. Motor and malignant diseases had the highest influence on performing everyday activities. On the other hand, these activities were least influenced by cardiovascular diseases. The worst assessment for the physical and psychological state was awarded by respondents with cancer, which was also reflected in low satisfaction. Respondents with cardiovascular or metabolic diseases perceived their physical and psychological health best. However, from the point of view of the assessment, it needs to be mentioned in which environment the respondents lived. E.g., respondents with cardiovascular diseases mostly stayed at the home setting, which could influence their assessment and their satisfaction with the state of health. Respondents with malignant diseases spent more time at hospitals or nursing homes, which can influence the assessment of their state of health. The results show that the patient subjective views of their own disease and associated issues need to be included both in the nursing care and in the comprehensive multidisciplinary care. This sensitive information cannot be obtained from any objective assessments performed in nursing care.